2022
DOI: 10.1186/s12912-022-01049-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of psychological first aid program on stress level and psychological well-being among caregivers of older adults with alzheimer’s disease

Abstract: Introduction Older adults with Alzheimer’s disease (AD) experience drastic changes in their physical and mental abilities. AD patients became heavily dependent on their caregivers for everyday functions, which have significant implications not only for them but also for their caregivers. So, many AD caregivers experienced an increased level of depression and anxiety symptoms, lower perceived control, and higher burden compared to non-AD caregivers. Therefore, psychological first aid (PFA) and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Positive interpersonal relationships, a subdomain, had the highest score of 3.75 ± 0.63 points, while autonomy had the lowest score of 3.17 ± 0.38 points. In a study of home-visiting caregivers during COVID-19, Kim et al [29,30] found a psychological well-being level of 3.33 points, similar to the results of this study. As the psychological wellbeing score of caregivers is moderate and not high, the development and implementation of a psychological well-being promotion program for caregivers caring for the elderly with dementia and other vulnerable groups is necessary [30].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Positive interpersonal relationships, a subdomain, had the highest score of 3.75 ± 0.63 points, while autonomy had the lowest score of 3.17 ± 0.38 points. In a study of home-visiting caregivers during COVID-19, Kim et al [29,30] found a psychological well-being level of 3.33 points, similar to the results of this study. As the psychological wellbeing score of caregivers is moderate and not high, the development and implementation of a psychological well-being promotion program for caregivers caring for the elderly with dementia and other vulnerable groups is necessary [30].…”
Section: Discussionsupporting
confidence: 89%
“…The psychological Well-Being Scale (PWBS) developed by Ryff [28] and adapted by Kim et al [29,30] into a Korean version was modified and used. The tool consists of a total of 43 questions, which are divided into six subdomains; seven questions on self-acceptance, seven on positive interpersonal relationships, seven on autonomy, seven on control over the environment, seven on life purpose, and eight on personal growth.…”
Section: Psychological Well-beingmentioning
confidence: 99%
“…The correlation between low education levels and the burden of caregiving appears to affect mainly women and has been reviewed elsewhere in excellent detail (Mielke, 2018). This burden on caregivers has been associated with the development of AD and other neuropsychiatric disorders, as highlighted in different studies (Shoukr et al, 2022;Hellis and Mukaetova-Ladinska, 2023). According to Figueroa et al (2021) digital health disadvantages women, particularly those from racial or ethnic minority backgrounds, due to limited access and exclusion from app creation, gender imbalance in digital health leadership, and detrimental gender stereotypes.…”
Section: Future Challenges and Recommendationsmentioning
confidence: 99%